2007
DOI: 10.1095/biolreprod.106.057851
|View full text |Cite
|
Sign up to set email alerts
|

The Cathepsin L First Intron Stimulates Gene Expression in Rat Sertoli Cells1

Abstract: Large amounts of cathepsin L (CTSL), a cysteine protease required for quantitatively normal spermatogenesis, are synthesized by mouse and rat Sertoli cells during stages VI to VII of the cycle of the seminiferous epithelium. We previously demonstrated that all of the regulatory elements required in vivo for both Sertoli cell- and stage-specific expression of the Ctsl gene are present within a ~3-kb genomic fragment that contains 2065 nucleotides upstream of the transcription start site and 977 nucleotides of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 62 publications
(89 reference statements)
2
17
0
Order By: Relevance
“…In addition, repeats in first introns were associated with greater expression divergence than repeats in other introns. This observation is consistent with previous work showing that most intronic regulatory regions occur in the first intron (Rohrer and Conley 1998), that the first intron has the highest divergence between human and chimpanzees (Gazave et al 2007), and that the first intron influences gene expression more than other introns (Jonsson et al 1992;Charron et al 2007).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, repeats in first introns were associated with greater expression divergence than repeats in other introns. This observation is consistent with previous work showing that most intronic regulatory regions occur in the first intron (Rohrer and Conley 1998), that the first intron has the highest divergence between human and chimpanzees (Gazave et al 2007), and that the first intron influences gene expression more than other introns (Jonsson et al 1992;Charron et al 2007).…”
Section: Discussionsupporting
confidence: 93%
“…The inclusion of just one intron near the 5′ end of the gene increases transcription of the gene many folds. A number of mammalian genes, including β-globin, growth hormone, thymidylate synthase, purine nucleoside phosphorylase, cathepsin L, and HIV-1 require introns for their normal expression (7)(8)(9)(10)(11)(12)(13)(14). A similar intron-dependent stimulation of transcription has been observed in a variety of genes in plants (6, 15).…”
mentioning
confidence: 78%
“…In contrast, splicing-dependent regulation of transcription requires a functional, splicing-competent intron within the body of the gene. Such introns cannot affect transcription if their splicing is compromised by a mutation in the conserved sequences at the 5′ splice site, 3′ splice site, branchpoint or if they are inserted in an antisense orientation (8,17). This direct effect of introns on transcription of genes is often referred to as "intron-mediated enhancement" (IME) and will be the focus of this investigation (6).…”
mentioning
confidence: 99%
“…However, introns are also required for optimal gene expression in many systems, including yeast, plants, insects, mammalian tissue culture cells, and transgenic mice. 13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28] In some cases, intron-dependent gene expression is mediated by transcriptional control elements. For example, previous studies in transgenic mice have implicated a role for intronic enhancers in mediating the expression of vascular endothelial growth factor receptor 2, Tie2, GATA2, and endoglin.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,26 Also, the requirement for intronic splicing depends on the identity of the promoter. 24,50 For example, introns were shown to be important for expression from immunoglobulin or b-globin promoters, but not from a heat shock promoter. 50 Consistent with these data, we demonstrated that the first intron of vWF was unable to augment expression of the Tie2-luciferase construct in transient transfections.…”
Section: Discussionmentioning
confidence: 99%